Grafting as a management tool to control Meloidogyne incognita in okra: Identifying rootstocks candidates - Costa Silva, Edgard Henrique [UNESP]; Soares, Renato S. [UNESP]; Diniz, Guilherme M. [UNESP]; Franco, Carolina A. [UNESP]; Marin, Marcus V. [UNESP]; Candido, Willame S. [UNESP]; Braz, Leila T. [UNESP]; Soares, Pedro Luiz M. [UNESP] (Elsevier, 2019)
The root-knot nematodes (RKN) challenge okra production (Abelmoschus esculentus L. Moench) worldwide and there are no reports of genetic resistance within the genus Abelmoschus. As an alternative, the compatibility for grafting of RKN-resistant malvaceous species with okra was assessed. Cotton (Gossypium spp.) genotypes are incompatible for grafting with okra. The kenaf (Hibiscus cannabinus L.), the false roselle (Hibiscus acetosella Welw. ex Hiern.) and the roselle (Hibiscus sabdariffa L.) are compatible. However, the rootstock must be sown five days after the scion to promote better grafting compatibility. The performance of grafted okra onto kenaf and false roselle was assessed in two experiments: RKN-free field in the open, and in the presence or not of Meloidogyne incognita race 3 in protected environment. The effect of grafting along time was addressed in the open field experiment. In RKN-free conditions, no differences were observed between rootstocks and self-grafted and non-grafted control. In the presence of M. incognita race 3, the resistant rootstocks provided superior plant development and production due low nematode reproduction. Therefore, grafting okra onto resistant rootstocks is a potential prophylactic measure to manage RKN.
Keywords: Abelmoschus esculentus L. Moench; Genetic resistance; Grafting compatibility; Intergeneric grafting; Meloidogyne spp.